The House that Engst Built - Dangerfield, Alison (Architectural History Aotearoa, 2010)
The German Moravian missionaries made a concerted foray into New Zealand in the nineteenth century. They travelled through the mainland and then went directly out to the Chatham Islands. One of the four to arrive there in 1843 was responsible for the only remaining architectural link with their mission. The German Mission House was designed by this missionary, Engst, who was committed to the idea of self reliance. He built it of locally quarried stone and several species of timber found locally, as well as kauri brought from the mainland. It was constructed in the 1860s - a functional, straightforward building, fit for its purpose. 150 years later, the German Mission House still stands facing the bleak northern coastline under the looming outcrop of Maunganui, visited regularly. It has been a home and trading post, and until a few years ago was inhabited. However in recent years it has been in danger of collapse. In early 2010, urgent conservation work was undertaken through the collaboration of many heritage professionals, going beyond the call, and interested locals, all urgently working to prevent its deterioration and collapse. The story of its conservation is one of efforts against the rugged climate.